Exploring the Effect of Red and Blue on Cognitive Task Performances - Xia, Tiansheng; Song, Lu; Wang, Ting T.; Tan, Ling; Mo, Lei (Frontiers in Psychology, 2016)
Previous studies on the effect of color on cognitive task performances and have led to two different views. Some researchers think that the influence of red and blue on cognitive tasks is modulated by the difficulty of the task, and other researchers suggest that the influence mainly depends on the type of task. The current study combined these factors to investigate the effect of color on cognitive task performance. In Experiment 1, we manipulated the difficulty of the task to investigate the effect of red and blue on detail-oriented task performance (the proofreading task), whereas in Experiment 2 we manipulated task difficulty to explore the effect of red and blue on creative task performance (the Remote Associates Test). The results showed that red enhanced the performance on a simple detail-oriented task. However, blue improved the performance on a difficult detail-oriented task as well as on both simple and difficult creative tasks. The results of the current study indicate that the type and difficulty of the task together modulate the effect of color on cognitive performances.